Forsvundet i 373 år - Andersen, Jesper Brandt (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2025)
The rediscovery of Karel van Mander’s painted portrait of Thomas Bartholin, which initiated a fruitful collaboration between a famous anatomist and a celebrated artist in 17th-century Copenhagen. In the Renaissance and the 17th century, not only science and religion but also science and art were inseparable. In Denmark, the mid-17th century was a flourishing time for anatomical science, which was supported by the science-loving Frederik III (1609-1670). It was precisely at the beginning of his reign that the physician and anatomist Thomas Bartholin (1616-1680) began his collaboration with the two court artists Karel van Mander (1609-1670) and Albert Haelwegh (1620-1673) – the first and most significant example of such a collaboration in Denmark. With their illustrations for Bartholin’s epoch-making publications on the lymphatic system, van Mander and Haelwegh helped create scientific history and an awareness of Danish anatomical research – an aware-ness that culminated in the following decade with the many anatomical discoveries of Bartholin’s pupil Niels Stensen (1638-1686). The starting point of Thomas Bartholin’s collaboration with Karel van Mander and Albert Haelwegh, Karel van Mander’s painted portrait of him, has now been rediscov-ered – in the Amsterdam Museum – having been lost for 373 years.